Safe pea to harvest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Grasspea (Lathyrus sativus L.; guaya in Ethiopia and gilban in Sudan) has long been known as a source of forage for animals. It grows mainly in north and north-east Africa, southern Europe, the Middle East and South Asia. It is rich in protein...